Multiple mediators of anxiety and depression between living space and cognitive function among elderly patients with ischemic stroke - Zhang, Yu; Yang, Xinyu; Gu, Qingxin; Pan, Jiawen; Mao, Jia; Lu, Dongyan; Zhou, Qing; Zhang, Lixiu (Frontiers in Psychiatry, 2025)
ObjectiveTo explore the relationship between living space, cognitive function, anxiety, and depression in ischemic stroke patients, specifically examining the mediating roles of anxiety and depression.MethodsA cross-sectional study included 445 ischemic stroke patients treated in the neurology department of a top-tier hospital in Zhejiang Province and discharged between January 2024 and January 2025 were selected. Participants completed General information questionnaires, the Montreal Cognitive Assessment (MoCA), Living Space Scale, and Hospital Anxiety and Depression Scale (HADS). Data were analyzed using R4.4.2 and MPLUS 8.7 software.ResultsAmong 445 participants, correlation analysis showed that cognitive function was positively correlated with living space (r = 0.37, P < 0.05) and negatively correlated with anxiety symptoms and depression symptoms (r = -0.53, r = -0.64, all P < 0.05). Anxiety and depression were mediating variables between living space and cognitive function (95%CI: 0.018~0.117, 0.017~0.095), with effect sizes of 0.072 and 0.057, respectively. Additionally, anxiety and depression played a serial mediating role between living space and cognitive function (95%CI: 0.082~0.172), with an effect sizes of 0.122.ConclusionLiving space level directly affect the cognitive function in ischemic stroke patients and indirectly affects cognition through its impact on psychological health, mediated independently and serially by anxiety and depression.